Aspiration can decline epidemic disease - Khadija Khatun; Md. Mamun-Ur-Rashid Khan; Jun Tanimoto (Alexandria Engineering Journal)
This study delves into the relationship between individual vaccination aspirations and their repercussions within the SEIRS epidemic framework, exploring effects on vaccination behavior, infection dynamics, and societal outcomes through the Vaccination Game concept. The co-evolution of epidemic dynamics and individual decision-making is examined, utilizing the social efficiency deficit (SED) to quantify a social dilemma. A novel aspiration-based model is compared with the conventional cost-based model. Higher aspiration levels correspond to increased vaccination rates, reducing overall infections. Contrary to assumptions favoring natural infection in low transmission scenarios, vaccination proves pivotal even in such contexts. Elevated transmission and immunity waning rates necessitate intensified vaccination for effective infection control, thereby reducing social dilemmas. Low vaccine efficiency coupled with high transmission rates escalates SED, but a specific vaccine efficacy threshold notably diminishes SED. Lower aspiration levels contribute to vaccine hesitancy, elevating SED, and infection rates. Surpassing an aspiration threshold redirects preferences towards vaccination, aligning with socially optimal scenarios and alleviating social dilemmas. The comparative analysis underscores the aspiration-driven approach outperforms in reducing SED, establishing its reliability in mitigating societal disease impact over the cost-based approach, but the optimal choice depends on specific epidemic conditions